Translation of Polysemous Words in Harry Potter (Journal of the College of Education for Women, 2019)
The paper pays attention to the polysemous words Harry Potter (HP). In this story, the present study exams some picking polysemic words to the extent that the translators of HP prevail to render the proposed significance as per the setting of the first content. Obviously, the picking translators in this examination were not mindful of the wonder of polysemy in the HP. They embrace a strict interpretation methodology to pass on the greater part of the polysemic sense. The method of data collection is divided into two stages. Firstly, determining the situational context of the fantasy and identifying the polysemic sense to clearly make all the contextual meanings of the source text. Secondly, reviewing the selected translation to examine how far they express the TL meaning of the polysemic sense. The present study clarifies that strict translation is reasonable to convey all components of the polysemic words. Furthermore, the translators need to utilize a selected methodology to conquer the confounding circumstance in deciphering polysemic words. In order to get a standard equivalence from multilingual dictionaries, comparative stylistic study functions to determine the contextual connotation and make the sense of polysemous notion.